Understanding the Emerging Role of Motorcycles in African Cities : A Political Economy Perspective - Kumar, Ajay (World Bank, Washington, DC, 2014)
A decline in organized public transport systems has led to rapid growth in non-conventional means of public transport, initially provided by minibuses and shared taxi/vans, and more recently by commercial motorcycles. Unlike cities in South and East Asia, ownership and use of motorized two-wheelers as a personalized vehicle is very small in sub-Saharan cities. However, over the past decade there has been a significant growth in the use of motorcycles as a commercial public transport mode. While offering certain transport advantages in the form of easy maneuverability, ability to travel on poor roads, and demand responsiveness, commercial motorcycle service growth has also led to an increase in road accidents, traffic management problems, pervasive noise and increases in local air pollution and greenhouse gas emissions. Government efforts to regulate the market have had the contrary impact of compounding the problem by distorting market structures. The growth in the use of commercial motorcycles has also dispelled one of the commonly held illusions: fare controls in the public bus market are often justified to support affordability for a vast majority of low income population; however, commercial motorcycles are more expensive than the lowest bus fares, but are increasingly being patronized by the poor due to the inadequacy of bus services. This paper attempts to evaluate the commercial motorcycle mode used in the three cities of Douala, Lagos, and Kampala, based on their political economy context in order to draw general conclusions of value throughout Africa and the rest of the developing world. The evaluation underscores the linkages between governance failure and weak sector performance and highlights the need to adapt policy instruments to local political and economic context. Central to discussion is the necessity to develop a participation framework driven by open communications across a wide spectrum of stakeholders.